A single night of partial sleep loss impairs fasting insulin sensitivity but does not affect cephalic phase insulin release in young men. (11th September 2015) - Cedernaes, Jonathan; Lampola, Lauri; Axelsson, Emil K.; Liethof, Lisanne; Hassanzadeh, Sara; Yeganeh, Adine; Broman, Jan‐Erik; Schiöth, Helgi B.; Benedict, Christian
Summary: The present study sought to investigate whether a single night of partial sleep deprivation (PSD) would alter fasting insulin sensitivity and cephalic phase insulin release (CPIR) in humans. A rise in circulating insulin in response to food‐related sensory stimulation may prepare tissues to break down ingested glucose, e.g. by stimulating rate‐limiting glycolytic enzymes. In addition, given insulin's anorexigenic properties once it reaches the brain, the CPIR may serve as an early peripheral satiety signal. Against this background, in the present study 16 men participated in two separate sessions: one night of PSD (4.25 h sleep) versus one night of full sleep (8.5 h sleep). In the morning following each sleep condition, subjects' oral cavities were rinsed with a 1‐molar sucrose solution for 45 s, preceded and followed by blood sampling for repeated determination of plasma glucose and serum insulin concentrations (−3, +3, +5, +7, +10 and +20 min). Our main result was that PSD, compared with full sleep, was associated with significantly higher peripheral insulin resistance, as indicated by a higher fasting homeostasis model assessment of insulin resistance index (+16%, P = 0.025). In contrast, no CPIR was observed in any of the two sleep conditions. Our findings indicate that a single night of PSD is already sufficient to impair fasting insulin sensitivity in healthy men. In contrast, brief oral cavity rinsing with sucrose solution did not change serum insulin concentrations, suggesting that a blunted CPIR is an unlikely mechanism through which acute sleep loss causes metabolic perturbations during morning hours in humans.